Retrospective response analysis of BAP1 expression to predict the clinical activity of systemic cytotoxic chemotherapy in mesothelioma. (January 2019) - Kumar, Neelam; Alrifai, Doraid; Kolluri, Krishna K.; Sage, Elizabeth K.; Ishii, Yuki; Guppy, Naomi; Borg, Elaine; Falzon, Mary; Nankivell, Matthew; Nicholson, Andrew G.; Janes, Sam M.
Highlights: BAP1 expression may correlate with response to vinorelbine in mesothelioma. BAP1 expression does not correlate with response to combination mitomycin, vinblastine and cisplatin. BAP1 expression should be assessed as a biomarker in ongoing prospective trials of vinorelbine in mesothelioma. Abstract: Introduction BRCA1 associated protein-1 (BAP1) is a key tumor driver in mesothelioma and a potential biomarker predicting response to several targeted therapies in clinical testing. Whether it also modulates response to cytotoxic chemotherapy is undetermined. This study used retrospective response analysis of BAP1 expression in archival tumor biopsies taken from patients in the MS01 trial (NCT00075699). We aimed to determine if BAP1 expression correlated with overall survival within the three treatment arms in this trial, namely active symptom control (ASC); ASC plus mitomycin, vinblastine and cisplatin (MVP); and ASC plus vinorelbine. Materials and methods We used immunohistochemical analysis of tumor samples from the MS01 trial to identify subgroups with and without nuclear BAP1 expression. We performed correlative analysis of clinical characteristics (age at diagnosis, sex and histological subtype) and overall survival within treatment arms with nuclear BAP1 expression. Results 89 tumor samples from the 409 patients originally in the trial were available for analysis. Of these, 60 samples harbored a positive internal control, in the form of positive staining of inflammatory cells for BAP1, and were carried forward for analysis. Correlative analysis suggested no significant association between loss of nuclear BAP1 expression and age at diagnosis, sex and histological subtype. Kaplan Meier survival analysis revealed a small, though non-significant, overall survival disadvantage associated with BAP1 expression in tumors from patients treated with vinorelbine. Discussion This exploratory analysis suggests BAP1 expression may modify response to vinorelbine in MPM, possibly due to prevention of mitotic microtubule formation. We suggest ongoing and planned clinical studies of vinorelbine in MPM assess BAP1 expression as a predictive biomarker of response.